Infusion of glucose and fructose in healthy horses - Hunka, Monica Miranda; Souza, Luzilene Araujo de; Santos, Fernando Leandro dos; Dantas, Waleska Ferreira; Manso, Helena Emília Cavalcanti da Costa Cordeiro; Abreu, José Mário Girão de; Ribeiro Filho, José Dantas; Manso Filho, Hélio Cordeiro (Revista Acadêmica Ciência Animal, 2018)
The aim of this study was to evaluate the metabolic response of five healthy non-pregnant Arabian mares to intravenous glucose or fructose infusions with commercial energy-boosting electrolyte supplements. The animals were kept on a dry lot and had free access to Tifton 85 hay, mineral salt and water. A full factorial experiment was carried out with five horses and five treatments, as follows: corn (control), fructose 25 g (Fru-25); fructose 50 g (Fru-50); glucose 25g (Glu-25); and glucose 50 g (Glu-50). The fructose and glucose solutions were infused into the jugular vein within 10 minutes, regardless of their volume, in doses ranging from 0.13 g/Kg (Fru-50 and Glu-50) to 0.07g/Kg (Fru-25 and Glu-25). Blood samples were drawn from the jugular vein at seven moments: 0 or pre-test (fasting), and 30, 60, 90, 120, 180, and 240 minutes after beginning the intravenous supplementation or food ingestion (corn). The following blood biomarkers were analyzed: glucose, insulin, aspartate aminotransferase (AST), alanine aminotransferase (ALT), phosphorus, total plasma protein (TPP) and insulin levels. The results were subjected to ANOVA and to Tukey’s test, with a p-value of 0.05, using SigmaPlot 13.0 software. The results indicated that glucose, insulin, ALT and AST levels differed significantly between treatments and blood sampling times. Only glucose showed high interaction between treatments and periods (p < 0.001). Glu-50 produced higher glucose concentrations at +30, +60 and + 90min. The insulin concentration was higher at +30 and + 60min in Glu-25, Fru-50 and Fru-25 (p < 0.05). On the other hand, there was no difference in total phosphorus and protein levels between treatments between the periods (p > 0.05). In conclusion, this research demonstrated that glucose or fructose infused into the bloodstream of healthy mares produced different glycemic and insulin curves when equivalent doses of commercial energy-boosting supplements were used.